Design and complexity. A multiscale approach for updating the project’s control tools - Fabio Conato; Valentina Frighi (Agathón)
In the current situation, it is necessary to propose an integrated, multiscale and multidisciplinary approach to manage the complexity of the architectural project, identifying decision support tools to perform multicriteria assessments between technical performance and different environmental criteria. This contribution presents the results of research activities undertaken in the framework of a PRRIITT within the Department of Architecture of the University of Ferrara, with the collaboration of the Larco Laboratory – High Technology Network of the Emilia Romagna Region and various companies, for the development of a method able to evaluate in a provisional way and during the design phase the different environmental quality components generated by the technological system, overcoming today simplification intrinsic in current assessment and certification models.